(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Bronchial asthma is a disease that causes chronic inflammation of the airways and causes difficulty in breathing. Bronchial asthma is a common problem in school-age children, and this disease can reduce the quality of life of children, limit their activities at school, and have a negative impact on their general health. Therefore, modern approaches to ambulatory treatment of bronchial asthma are important.